Існування і наближена побудова розв'язків крайових задач - Король, І.І.; Перестюк, М.О. (Видавничий дім "Академперіодика" НАН України, 2007)
A new numerical-analytic method for investigating the boundary-value problems for nonlinear differential systems is suggested.